Negatively Speaking: a sociolinguistic feature of Newfoundland Speech - O’Dwyer, Bernard (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1989)
Native Newfoundland speakers often times use the negative declarative ending in a tag question when extending an invitation. Where one might expect to hear, ’Would you like a cup of tea?’ , you often hear, ’You don’t want a cup of tea, do you?’. This use of a negative proposition ending in a tag question does not signal that a negative response is expected. The invitation, I propose, is really quite positive in intent. The use of the negative here signals, instead, the social features of politeness and possibly inferior position to the addressee.